2014
DOI: 10.1007/s00216-014-8007-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of monolithic poly(N-vinylcarbazole-co-1,4-divinylbenzene) capillary columns for the separation of small molecules

Abstract: Short-term polymerization or the so-called low-conversion polymerization was applied for the preparation of N-vinylcarbazole (NVC) and 1,4-divinylbenzene (DVB) monolithic capillary columns. The synthesis was carried out by thermally initiated free radical copolymerization under the influence of inert micro- (toluene) and macroporogen (1-decanol) and α,α'-azoisobutyronitrile (AIBN) as radical initiator. The morphological and porous properties were studied by scanning electron microscopy (SEM), nitrogen adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…We have demonstrated, that hypercross‐linked styrene‐based polymer monolith with grafted polar functionality do not change its properties even after 10 000 injections of test compounds . Also monolithic columns prepared by short polymerization reaction times with the most dominant effect of reaction kinetics provide repeatable and robust column properties . Actually, the vast majority of articles cited thorough this review provided a part devoted to columns preparation repeatability confirming that polymer‐based monoliths are very robust and stable stationary phases.…”
Section: Polymer‐based Monolithic Stationary Phasesmentioning
confidence: 73%
See 3 more Smart Citations
“…We have demonstrated, that hypercross‐linked styrene‐based polymer monolith with grafted polar functionality do not change its properties even after 10 000 injections of test compounds . Also monolithic columns prepared by short polymerization reaction times with the most dominant effect of reaction kinetics provide repeatable and robust column properties . Actually, the vast majority of articles cited thorough this review provided a part devoted to columns preparation repeatability confirming that polymer‐based monoliths are very robust and stable stationary phases.…”
Section: Polymer‐based Monolithic Stationary Phasesmentioning
confidence: 73%
“…An early termination of a polymerization reaction is one of the simplest ways how to control both porous properties and related efficiency of polymer monoliths . Koeck et al utilized short‐term free‐radical polymerization and prepared poly(N‐vinylcarbazole‐ co‐ divinylbenzene) capillary columns for the separation of small molecules . Monomers conversion analysis revealed that while N‐vinylcarbazole is consumed linearly with longer polymerization time, divinylbenzene reaches conversion of 90% already after 90 min of polymerization reaction.…”
Section: Polymer Monoliths For Separation Of Small Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Low conversion polymerization (i.e., short‐term polymerization) has been applied for the preparation of poly( N ‐vinylcarbazole [NVC]‐ co ‐1,4‐divinylbenzene [DVB]) using NVC as the functional monomer and DVB as the cross‐linker . Applying this approach in combination with variation in the radical initiator content proved to have a noticeable impact on the porous properties of the newly developed poly(NVC‐ co ‐DVB) stationary phase.…”
Section: Nonpolar Organic Monolithsmentioning
confidence: 99%